Animal–plant–microbe interactions : direct and indirect effects of swan foraging behaviour modulate methane cycling in temperate shallow wetlands - P Bodelier; M Stomp; L Santamaria; Marcel Klaassen; H Laanbroek (2006)
Wetlands are among the most important ecosystems on Earth both in terms of productivity and biodiversity, but also as a source of the greenhouse gas CH 4 . Microbial processes catalyzing nutrient recycling and CH 4 production are controlled by sediment physico-chemistry, which is in turn affected by plant activity and the foraging behaviour of herbivores. We performed field and laboratory experiments to evaluate the direct effect of herbivores on soil microbial activity and their indirect effects as the consequence of reduced macrophyte density, using migratory Bewick’s swans ( Cygnus columbianus bewickii Yarrell ) feeding on fennel pondweed ( Potamogeton pectinatus L. ) tubers as a model system. A controlled foraging experiment using field enclosures indicated that swan bioturbation decreases CH 4 production, through a decrease in the activity of methanogenic Archaea and an increased rate of CH 4 oxidation in the bioturbated sediment. We also found a positive correlation between tuber density (a surrogate of plant density during the previous growth season) and CH 4 production activity. A laboratory experiment showed that sediment sterilization enhances pondweed growth, probably due to elimination of the negative effects of microbial activity on plant growth. In summary, the bioturbation caused by swan grazing modulates CH 4 cycling by means of both direct and indirect (i.e. plant-mediated) effects with potential consequences for CH 4 emission from wetland systems.